2008
DOI: 10.1016/j.joms.2008.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Carcinomas Found Incidentally in the Cervical Lymph Nodes: Do They Arise From Heterotopic Thyroid Tissues?

Abstract: Purpose: Thyroid carcinomas have been incidentally found in the cervical lymph nodes during operation of head and neck squamous cell carcinoma (SCC) and such carcinomas have been considered metastatic. Patients and Methods:We encountered 3 cases of incidental papillary carcinoma in the neck of patients with oral SCC and reviewed 75 cases previously reported.Results: Papillary carcinomas were found in 3, 10 and 3 lymph nodes in cases 1, 2 and 3, respectively. CT examination revealed 2 tumor-like shadows and 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…15 There is, however, continued controversy as to whether thyroid tissue in lymph nodes represent metastasis or whether they are mere benign inclusions. We would like to stress that if benign thyroid exists in neck nodes it is not in lateral nodes but in median ones.…”
Section: Discussionmentioning
confidence: 99%
“…15 There is, however, continued controversy as to whether thyroid tissue in lymph nodes represent metastasis or whether they are mere benign inclusions. We would like to stress that if benign thyroid exists in neck nodes it is not in lateral nodes but in median ones.…”
Section: Discussionmentioning
confidence: 99%
“…Many thyroid carcinomas found incidentally in the cervical lymph nodes are considered to arise from heterotopic thyroid tissue . The observed well‐formed thyroid tissue in this case was not compatible with the option of heterotopic thyroid tissue into nodes.…”
mentioning
confidence: 58%
“…[7][8][9] It has also been suggested that thyroid carcinoma in cervical lymph nodes may not necessarily be metastatic lesions but may arise from transformed heterotopic thyroid tissue. Benign-looking thyroid tissue found incidentally in cervical lymph nodes has also been described in the past, [10][11][12] but it may reflect metastatic follicular variant of well-differentiated PTC. Thus, whenever normal thyroid-like tissue is identified in an excised lymph node removed for nonthyroid-related surgery, appropriate work up should always be undertaken to rule out a primary PTC.…”
Section: Introductionmentioning
confidence: 85%